Analisis Sistem Informasi Berbasis Web pada Manajemen Inventaris Produk Toko Kelontong - Surachman, Arie (Jurnal Esensi Infokom : Jurnal Esensi Sistem Informasi dan Sistem Komputer, 2024)
One of the goals to advance grocery store owners is by developing an inventory management information system for their sales. The purpose of this research is to design a web-based application system for grocery stores. It will be able to help sales and promote products. One of the important features that can be utilized by grocery store owners is the inventory product management feature. In the development of this system, the researcher used the PHP programming language, which is used to build web applications, while the database used is MySQL. The system development methodology used by the researcher is the Waterfall methodology. The Waterfall methodology has several stages, including Analysis, System Design, Implementation, Integration, Operation, and Maintenance. In the data collection process, the researcher used the observation method. The output that will be generated from the development of this system is a web-based product inventory application